Critical Analysis of Dental Care and Treatment Modalities - Almuqhim, Suliman Muqhim; Nawwab, Majed Abdulhafeez; Alsinaidi, Yousif Abdullah; Alshalan, Ahad Ali; Alsinaidi, Elaf Abdullah; Ghamdi, Ayedh Bakhit Al; Alshammari, Mohammed Aqeel; Alshammari, Abdullah Hameed; alshammari, Mohammed zaben bas; Bushnaq, Abdulaziz Mohammed; Turkistani, Yazeed Mohammed (Journal of Ecohumanism, 2024)
Oral health is an important part of the human body's organizational health and may have physical and psychological effects. In the past decades, dental health care and its practices have somehow developed and improved the overall health of dental treatments. Nevertheless, some changes have borne the following challenges: accessibility, affordability, and incorporating new technologies. This paper aims to describe, analyses and analyze the most common dental care practices and appraise the different types of dental therapies applied in contemporary dentistry. It looks at how dental treatments have been practiced over the years, enhanced technology found in dentistry, and the current issues permeating this field of health study. Based on a review of the literature and an analysis of results and findings, the paper provides new perspectives on how dental care should be further developed for the continuously expanding demand for diverse population groups. Finally, suggestions for increasing receipt of adequate dental care and fine-tuning approaches to therapy in the future are given.